Diagnostic value of blood variables following attenuation of congenital extrahepatic portosystemic shunt in dogs. (29th October 2019) - Vallarino, Nicolas; Pil, Steven; Devriendt, Nausikaa; Or, Matan; Vandermeulen, Eva; Serrano, Gonçalo; Paepe, Dominique; Bosmans, Tim; de Rooster, Hilde
Abstract : Background: The aims of this study were to determine if extrahepatic portosystemic shunt (EHPSS) postoperative closure could be predicted based on preoperative blood analyses and to determine the accuracy of blood variables to evaluate persistence of portosystemic shunting postoperatively (multiple acquired portosystemic shunts (MAPSS) or persistent EHPSS). Methods: Retrospectively, 62 dogs treated surgically for congenital EHPSS that underwent postoperative trans‐splenic portal scintigraphy or CT angiography three to six months postoperatively were included. Results: None of the studied preoperative blood variables could unambiguously predict surgical outcome. Elevated postoperative fasting venous ammonia (FA) concentration always indicated surgical failure (persistent shunting or MAPSS), but normal FA did not provide any information on the postoperative shunting status. Paired serum bile acids (SBA) were not reliable enough to confirm or exclude postoperative shunting. In the presence of low normal postoperative FA levels, elevated preprandial SBA was more likely in dogs with persistent shunting (sensitivity of 0.79, specificity of 0.83), whereas postprandial SBA below reference limit was more often observed in case of surgical success (sensitivity of 0.93, specificity of 0.67). Conclusion: Blood variables, and more specifically the combination of FA and SBA, are not a valuable alternative to advanced medical imaging to reliably assess the surgical outcome after EHPSS surgery.